Stability characterizations of feed-based bivalent vaccine containing inactivated Streptococcus agalactiae and Aeromonas hydrophila against streptococcosis and Aeromonas infections in red hybrid tilapia (Oreochromis sp.) - Mohd Ali, Nur Shidaa; Ngalimat, Mohamad Syazwan; Saad, Mohd Zamri; Amal, Mohammad Noor Azmai; Salleh, Annas; Zulperi, Zarirah; Md Yasin, Ina Salwany (Springer Science and Business Media Deutschland, 2024)
Feed-based bivalent vaccine (FBBV) containing killed whole organism (KWO) of Streptococcus agalactiae and Aeromonas hydrophila with 10% palm oil was previously proved to improve red hybrid tilapia’s (Oreochromis sp.) immunity against streptococcosis and Aeromonas infections. This study characterized the FBBV’s stability following the preparatory process and storage. The FBBV was prepared, and the KWO’s stability was determined microscopically and molecularly. The efficacy of FBBV stored at room temperature (25±2 °C) for 0, 30 and 60 days was investigated in red hybrid tilapia. The results indicated the addition of palm oil was not affecting the KWO’s structure and helping in the FBBV’s pelletization. In 1 g of FBBV contained 1.5×109 CFU/g of S. agalactiae and 4.9×109 CFU/g of A. hydrophila, respectively, even after 60 days of storage at room temperature. The KWO’s structure in FBBV was not affected following in vitro acidic tolerance analysis, as noted from light and electron microscopies. The FBBV’s carbohydrate, energy, moisture, total protein and total ash contents remained stable at 95% after 60 days of storage at room temperature, while the KWO’s concentration was slightly reduced to 83.3% for S. agalactiae (1.25×109 CFU/g) and 80.6% for A. hydrophila (3.85×109 CFU/g), respectively. Fish vaccinated with FBBV that was stored for 0, 30 and 60 days did not show any significant differences (p≥0.05) in the relative percent survival when challenged with pathogenic Streptococcus spp. and Aeromonas spp. These findings suggested that the FBBV is a stable vaccine, which underscores its potential application as aquatic vaccines in aquaculture.